Use the property of the logarithms : lnA + lnB = lnAB
ln(x) +ln(x+3)=1
ln[x(x+3)]=1
Now "antilog" the equation, meaning do the:
e^(LHS) = e^(RHS)
and simplify
x(x+3) = e¹
x² + 3x - e = 0
Use the quadratic formula
x = [-3 ± √(9 + 4e)] / 2
Type this into your calculator if you want, to get
x = [-3 + √(9 + 4e)] / 2 = 0.729
and
x = [-3 - √(9 + 4e)] / 2 = -3.729
we omit the latter solution (-3.729) because log of a negative number cannot be taken.
Hope this helps.
2007-04-29 08:54:02
·
answer #1
·
answered by M 6
·
6⤊
0⤋
ln(x) + ln(x+3) = 1
ln(x+3) = 1 - ln(x)
e^(ln(x+3)) = e^(1 - ln(x))
x+3 = (e^(1))/(e^(ln(x)))
x+3 = e/x
(x+3)*x = e
x^2+3x -e =0
use quadratic equation
x = (-3+-sqr(9+4e)) / 2
x= (-3+sqr(9+4e)) / 2 only because the other one whould yeild a negative number any you cant do the natural log of a negative number
2007-04-29 16:04:47
·
answer #2
·
answered by Marc M 1
·
0⤊
0⤋
Ln[x(x+3)] = 1
x(x+3) = e
x^2 + 3x - e = 0
Solve using the genarl law
x = [-3 + sqrt ( (9 + 4e)]/2 = 0.728964295
or
x = [-3 - sqrt ( (9 + 4e)]/2 = - 3.728964295
2007-04-29 16:06:17
·
answer #3
·
answered by a_ebnlhaitham 6
·
0⤊
1⤋
ln(x) + ln(x + 3) = 1
ln[x(x - 3)] = 1
x² - 3x = e
x² - 3x - e = 0
x = [3 ± â(9 + 4e)] / 2
Since a log can't be taken of a negative number,
x = [3 + â(9 + 4e)] / 2
2007-04-29 16:03:40
·
answer #4
·
answered by Louise 5
·
0⤊
0⤋
Exponentiate both sides, to get x(x+3) = e, so x*2 + 3x - 2.718 = 0, which is solvable by the quadratic formula in the usual way.
2007-04-29 15:57:50
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
ln (x.(x + 3)) = 1
x.(x + 3) = 2.718
x² + 3x - 2.718 = 0
x = [- 3 ± â(9 + 10.9)] / 2
x = [- 3 ± â(19.9)] / 2
x = 0.73 , x = - 3.73
2007-04-29 16:05:11
·
answer #6
·
answered by Como 7
·
0⤊
1⤋
Help, mI use to could do this
2007-04-29 16:07:28
·
answer #7
·
answered by flower wanda 3
·
0⤊
1⤋